Influence of viscosity modifying agent on some rheological properties, segregation resistance and compressive strength of self-compacting concrete - Grabiec, Anna M. (Journal of Civil Engineering and Management, 2013)
Rheological properties of self-compacting concrete mixes containing a viscosity modifying agent (VMA) in their composition were studied. After preliminary studies self-compacting concrete mixes and, particularly, a fluid concrete mix prone to segregation of its ingredients were chosen. VMA was added in various amounts to that concrete mix to check how it performed in fresh and hardened concrete. Main studies focused on the influence of VMA on the following properties of concrete mixes: the slump flow, the flow time into the diameter of 500 mm and the resistance to segregation in the vertical direction. Moreover, the air content of concrete mixes and the 28-day compressive strength of concrete were measured. Test results showed that VMA significantly influenced the rheological properties of concrete mix, stabilised it and reduced the segregation. It was proved, that the concrete mix modified by VMA used in the optimal amount, featured the smallest scatter of concrete strength results. Besides, the Tukey's test showed that a reduction of the concrete compressive strength is possible to be statistically insignificant when compared to the reference level.First published online: 19 Oct 2012